QUALIFICATION REQUIREMENTS FOR THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF THE SUBJECT "TECHNOLOGY" - William I.K. (International Journal of Literature and Language Studies, 2022)
In this article, the methodical preparation of future technology teachers for teaching, the processes of determining the state educational standard and qualification requirements for technological education, and students' mastery of the subjects in the curriculum are discussed. and in the development of professional competence of future technology teachers, we have demonstrated the process of professional competence development based on digitized educational resources.